Gaze behaviour in elite gymnasts when performing mini-trampoline and mini-trampoline with vaulting table - a pilot study - Pereira de Sousa de Carvalho Barreto, J. F.; Martins Casanova, F. L.; Duarte Peixoto, C. J. (Science of Gymnastics Journal, 2020)
Visual system provides information from the environment, leading gymnasts to improve performance. The question of what sources of visual information from the environment contribute to performance, remains unclear. This study aims to analyse visual behaviour, as areas of interest, fixated by Teamgym elite gymnasts during the performance of techniques on mini-trampoline and mini-trampoline with vaulting table. We hypothesised that: a) gymnasts would fixate areas of interest in the environment to visually perceive relevant information, b) fixations on the area of interest "landing mat" would occur during the last part of flight phase and landing. Three teamgym elite gymnasts performed three tasks on mini-trampoline and one task on mini-trampoline with vaulting table. The variables were: fixation duration (FD), areas of interest (AOIs), ratio between total fixation duration and total task duration (TFD/TD) and ratio between total fixation duration per AOI and total fixation duration (TFDA/TFD). Results showed that TFD/TD increased with the decreased of complexity degree for all tasks. Mini-trampoline was the most fixated AOI (except for straight barani out on mini-trampoline) while wall was the less fixated. The run-up zone was the most fixated zone. For the task on mini-trampoline with vaulting table, participants reduced the time spent fixating run-up zone and increased time spent fixating mini-trampoline and vaulting table. Landing mat was the only AOI that was fixated during the flight phase. Results suggest that gymnasts may adapt their visual strategy to the degree of complexity of the task, as reflected in the results of TFD/TD and TFDA/TFD.